2014
DOI: 10.1098/rspb.2014.0075
|View full text |Cite
|
Sign up to set email alerts
|

Heterostyly accelerates diversification via reduced extinction in primroses

Abstract: The exceptional species diversity of flowering plants, exceeding that of their sister group more than 250-fold, is especially evident in floral innovations, interactions with pollinators and sexual systems. Multiple theories, emphasizing flower-pollinator interactions, genetic effects of mating systems or high evolvability, predict that floral evolution profoundly affects angiosperm diversification. However, consequences for speciation and extinction dynamics remain poorly understood. Here, we investigate traj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
121
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(130 citation statements)
references
References 81 publications
(136 reference statements)
7
121
2
Order By: Relevance
“…Its occurrence in self-compatible, monomorphic (i.e., homostylous) primrose species that evolved from obligately outcrossing, heterostylous ancestors (Mast et al 2006;de Vos et al 2014ade Vos et al , 2014b) is therefore enigmatic. The loss of traits that enforce outcrossing is thought to be favored in environmental conditions where outcrossing opportunities are limited due to mate limitation and/or pollinator limitation, so that autonomous selfing may provide reproductive assurance (Eckert et al 2006;Busch and Delph 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its occurrence in self-compatible, monomorphic (i.e., homostylous) primrose species that evolved from obligately outcrossing, heterostylous ancestors (Mast et al 2006;de Vos et al 2014ade Vos et al , 2014b) is therefore enigmatic. The loss of traits that enforce outcrossing is thought to be favored in environmental conditions where outcrossing opportunities are limited due to mate limitation and/or pollinator limitation, so that autonomous selfing may provide reproductive assurance (Eckert et al 2006;Busch and Delph 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Selfed progeny are frequently less fit than outcrossed progeny due to inbreeding depression, which is largely caused by the expression of deleterious recessive alleles in homozygotes that rise in frequency due to selfing (Charlesworth and Willis 2009). In addition, sustained high levels of selfing can also decrease genetic variation in populations (Hamrick and Godt 1996), which may affect macroevolutionary patterns of diversification (Stebbins 1974), for instance, through increased extinction risk (Goldberg et al 2010;Igić and Busch 2013;de Vos et al 2014a). Theoretical studies emphasized individual reproductive fitness components (i.e., number of selfed ovules, outcrossed ovules, and ovules fertilized through pollen export) and suggested that functional interactions or trade-offs between them predict many possibilities for intermediate selfing rates that are evolutionarily stable (Harder and Routley 2006;Johnston et al 2009;Devaux et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, sampling at the genus level could potentially bias our assessment of the transition rates by ignoring infrageneric variation of the sexual condition in the 74 (25%) polymorphic genera. In angiosperms, self-compatible species appear at the tips of the tree because of higher rates of extinction in selfcompatible lineages, as demonstrated by Goldberg et al (2010) and De Vos et al (2014). Sampling genera as terminal units could lead to biased sexual transition rates because of high rates of extinction of bisexual lineages, so that many transitions towards bisexuality would be hidden.…”
Section: Data Collectionmentioning
confidence: 99%
“…Earlier preliminary pollen morphological studies showed that Androsace and three related genera ( Pomatosace , Douglasia , and Vitaliana ) have a unique pollen type within Primulaceae (the “ Androsace ‐type”), in which the pollen grains are prolate and tricolporate (Wendelbo, ; Spanowsky, ). The results of recent molecular phylogenetic studies based on DNA sequences also support the view that this group of these four genera constitute a major clade of Primulaceae (KĂ€llersjö et al, ; Mast et al, ; Trift et al, ; Martins et al, ; de Vos et al, ). Wang et al () and Schneeweiss et al (); who respectively focused on the Himalayan and European species of Androsace , obtained similar results: (i) the entire Androsace group, comprising Androsace , Pomatosace , Douglasia and Vitaliana , comprise a clade; (ii) species in the Asian sect.…”
mentioning
confidence: 63%